Predictive Models of Attitude toward Homosexuality in Heterosexual Men - Moral de la Rubia, José; Facultad de Psicología, UANL. (2014)
The aims of this paper were to predict membership to a group of attitude of acceptance or ambiguity-rejection toward homosexuality, and describe the attitude levels. The Attitudes Toward Lesbians and Gay men (ATLG) scale was applied to a non-probability sample of 239 single heterosexual men. All of them were students of health sciences. 15% expressed rejection (including 4% extreme) based on the ATLG total score. Rejection toward gay men (28% including 7% extreme) was higher than toward lesbians (9% including 2.5% extreme). Not having homosexual friends and having adscription to Christian or Catholic religions were significant predictors of belonging to the group with an ambiguity-rejection attitude. It is concluded that the percentage of rejection toward homosexuality is significant. For this reason it is encouraged to implement workshops for promoting an acceptance attitude, and consider these risk variables in their design.